IS ANTENATAL CARE (ANC) EXAMINATION IMPORTANT FOR THE HEALTH OF THE MOTHER AND BABIES? - Sari, Wahyu Anjas; Nurwati, Ida (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2023)
Background: Maternal mortality and infant mortality are conditions that require special attention and immediate treatment. The antenatal care program is one way to reduce the increase in maternal mortality and infant mortality. Objective: This study aims to determine the importance of antenatal care examinations on the health of mothers and babies. Design: Scoping review was used in preparing this literature review. Data Sources: The researchers conducted a search using several search engines, including Google Scholar, DOAJ, Pubmed, EBSCO, and Sciencedirect with several inclusion criteria, including 1) Year of publication between 2019-2023, 2) Articles in English and Indonesian, and 3) Original articles, full text, and open access. Review Methods: The researchers carried out descriptive analysis and synthesis of the contents of all the articles, so that the researchers would be able to conclude the results of each research used as material in preparing this literature review. Results: Based on the results of the search conducted by the researchers, it was found that 5 articles were in accordance with the objectives of preparing this literature review. These articles show the importance of antenatal care (ANC) examinations for the health of mothers and babies, both during pregnancy and after birth. Conclusion: Implementing antenatal care services for pregnant women is very important because it can be related to the health of the mother and baby right up to the birth process. Apart from that, antenatal care services can detect early postnatal health problems, such as Low Birth Weight (LBW), Stunting, and so on.